Gabapentin and Baclofen Polypharmacy Presenting as Non-specific Abdominal Pain and Hyper-Reflexivity: A Case Report - Varun Sharma; Likith Surendra; Milan Sivakumar; Thomas Varkey; Avtar Singh (Neurology Letters, 2025)
Introduction: Gabapentin is a relatively safe medication and is frequently prescribed in large doses - upwards of 3600 mg per day. This along with baclofen are frequently prescribed together in patients suffering from neuropathy and muscle spasms. Despite these medications being widely known to be non-toxic, various case reports have outlined significant side effects secondarily to the use of these higher doses of medication. This in combination with other drugs (polypharmacy) can cause a toxidrome with both enteric and neurologic complications which is often overlooked.Case Presentation: Herein, the authorial team discusses a 69-year-old patient who presented to an acute on chronic worsening of his long-standing non-specific abdominal symptoms of generalized pain and discomfort which lessened but did not resolve with defecation. During the history taking, careful questioning revealed that the patient had an increase in gabapentin dosage to the highest clinically indicated dosage of 3600 mg per day roughly one month prior in tandem with the use of 30 mg per day of baclofen. Along with the patient’s chief complaint and history, a crucial physical exam with various neurological abnormalities, imaging, and lab findings helped cue the team into recognizing these symptoms as signs of a polypharmacy reaction. The patient’s dosage of both medications were tapered which led to demonstrable clinical improvement of both the abdominal symptoms and the neurological symptoms,Conclusions: This case report demonstrates the importance of a careful and complete history and physical examination when working with patients presenting to the emergency room with non-specific abdominal symptoms. The authorial team wants to highlight the importance of a broad differential to ensure that patients receive appropriate care. Lastly, only through the carefully crafted and thorough physical examination and history were the team able to narrow the differential and eventually find the correct diagnosis.